EVALUATION OF METHODS FOR TOTAL RNA EXTRACTION FROM THE ENDOSPERM OF COCOS NUCIFERA VAR. MAKAPUNO IN VIETNAM FOR MOLECULAR ANALYSIS - Thanh-Diem Nguyen; Huyen-Trang Vu (BIOTROPIA, 2023)
Sap coconut (Cocos nucifera L. var. makapuno) in Vietnam is a mutant coconut variant; coconut water is in the state of lotus glue, and coconut rice is like cream. For high-quality transcriptome, sequencing, quality, purity and concentration of RNA are the key factors. However, coconut endosperm tissue has higher stiffness and fatness than the leaf tissue, which complicates the extraction process. Moreover, RNA is much more difficult to preserve than DNA. In this study, various RNA extraction methods were examined in Vietnamese waxy coconut endosperm tissue samples. Optimum extraction and preservation of the RNA using the simplest possible chemicals was the objective of this study. The modified CTAB method with LiCl and the TRI reagent method were tested and evaluated. The purity, concentration and quality of RNA after storage were improved. The findings indicated that the TRIsure extraction method with the addition of NaCl and β-mercaptoethanol yielded optimum RNA quality. The RNA concentration was 159 ng/µL, with a purity ratio of 1.94 ± 0.04 for A260/A280 and 1.58 ± 0.02 for A260/230. RNA samples remained stable for up to 3 weeks when stored in absolute ethanol at 8°C–10°C, which significantly reduced their degradation during transportation. This study facilitated the use of simple chemicals for high-quality RNA extraction from coconut endosperm and its preservation for applications in high throughput sequencing.